Effects of acute aerobic exercise on NADPH oxidase levels in trained male subjects - Algul, Sermin; Arihan, Okan; Ozcelik, Oguz (Yuzuncu Yil Universitesi Tip Fakultesi, 2018)
Exercise induced muscle activity causes increase in oxidative stress and free radical levels. Cardiac and skeletal muscle activity results in elevated NADPH oxidase levels in body. In the present study, we intended to evaluate NADPH oxidase levels in response to the aerobic exercise performed in the morning and at night in trained male subjects. Total of 10 healthy trained subjects (age: 19.3±0.7 years and height: 171.8±2.2cm) performed 2 aerobic running exercise in the morning and at night on different days. Venous blood samples were taken at onset and after exercise. NADPH oxidase levels were measured using ELISA method. NADPH oxidase levels were found as 355.17±48.65 nmol/L at basal and increased to 374.42±47.41 nmol/L (p<0.0001) in morning exercise. In addition, it was 353.42±56.07 nmol/L at basal and increased to 3 68.68±55.12 nmol/L after exercise at night (p<0.0001). During exercise, observation of increased percent of NADPH oxidase levels was 6.20±1.8 % in morning and 6.28±1.3 % in night exercise, and no statistical significance was found (p=0.2). As a result, acute aerobic exercise may cause an increase in NADPH oxidase levels in trained subjects but it was not dependent with the time of exercise. © 2018, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Aerobic fitness; Exercise; Free radicals; NADPH oxidase